Der sanfte Trug des Berner Milieus : Künstler und Emigranten 1910-1920 - Helfenstein, Josef; von Tavel, Hans Christoph; Kunstmuseum Bern, Bern (Bern : Kunstmuseum Bern, 1988)
Amiet, Cuno ; Balmer, Wilhelm ; Bangerter, Walter ; Boss, Eduard ; Brack, Max ; Brügger, Arnold ; Buri, Max ; Cardinaux, Emil ; Clénin, Walter ; Colombi, Plinio ; Eggimann, Hans ; Fink, Waldemar ; Frey-Surbek, Marguerite ; Gehri, Karl ; Gloor, Alfred ; Hänny, Karl ; Haller, Hermann ; Heer, August ; Hodler, Ferdinand ; Itten, Johannes ; Jordi, Eugen ; Klee, Paul ; Kreidolf, Ernst ; Lauterburg, Dora ; Lauterburg, Martin ; Leuenberger, Ernst ; Linck, Ernst ; etc.
Der sanfte Trug des Berner Milieus : Künstler und Emigranten 1910-1920, Kunstmuseum Bern, 26. Februar bis 15. Mai 1988
boek